The impact of biofertilizer technology adoption on the faba bean productivity in the central highlands of Ethiopia: The propensity score matching model - Getachew Chala; Bezabih Emana; Daniel Masresha (PLoS ONE, 2025)
Adoption of organic fertilizer technology increases crop productivity through replenishing the soil with natural organic nutrient as compared to in-organic chemical that is costly and damaging the soil fertility in the long run. Few studies have been documented on the contribution of bio-fertilizer on crop productivity on the plots of smallholder households. This study investigates the impact of adoption of bio-fertilizer technology on the faba bean productivity in the central highlands of Ethiopia, particularly in rural districts surrounding Addis Ababa, Ethiopia. The study is limited to small holder faba bean farmers in the central highlands of Ethiopia due to the diversified agro-ecology, socioeconomic, cultural and institutional factors in the country; it would be difficult to conduct a study on a specific area and generalize for others. A multi-stage sampling method was utilized to select 384 households for the sample. The primary data for the study was collected with a face to face interview using structured questionnaire. Propensity score matching (PSM) technique was employed to evaluate the impact of adoption of bio-fertilizer on faba beans productivity in the study area. The finding of the research revealed that, biofertilizer adoption on average increased faba bean productivity of adopters by about 5.1 quintals ha-1 than the non-adopters. Thus, based on the finding of the study, it is recommendable to strengthen existing extension service to promote the use of biofertilizer.